Correlation between referral cytology and in-house colposcopy-guided cytology for detecting early cervical neoplasia - Schulmeyer, Carla; Stübs, Frederik; Gaß, Paul; Renner, Stefan; Hartmann, Arndt; Strehl, Johanna; Mehlhorn, Grit; Geppert, Carol-Immanuel; Adler, Werner; Beckmann, Matthias; Koch, Martin (Archives of Gynecology and Obstetrics, 2019)
Purpose: The current cervical cancer screening program in Germany recommends that the results showing suspected HPV infection should be further examined in specialized colposcopy units. This study aimed to correlate externally documented Pap smear results with in-house colposcopy-guided Pap cytology results and compare colposcopy-guided biopsy and postoperative histopathology results. Methods: Clinical data were analyzed from 3627 examinations in 2844 patients who visited a university certified dysplasia unit from 2014 to 2017; 2212 patients underwent complete assessments, including Pap smear, colposcopy, HPV testing, colposcopy-guided biopsy, and/or surgery. The results were analyzed descriptively. Results: External and in-house Pap results were consistent in 1054 ofthe 2212 patients (47.65%). Referral cytology showed a higher grade than in-house in 456 (20.61%) and a lower grade in 702 (31.74%). Using the histopathological findings as the gold standard, overdiagnosis in the referral cytology was noted in 180 patients (13.19%), underdiagnosis in 263 (19.27%), and concordant findings in 922 (67.55%). For in-house cytology, overdiagnosis was found in 133 patients (10.74%), underdiagnosis in 192 (15.51%), and accurate diagnosis with congruent cytology and histopathology findings in 913 (73.75%). Conclusions: The rate of detection of cervical abnormalities differs significantly depending on whether the examination is performed routinely or in specialized units. Colposcopy-guided Pap smears correlate significantly better with histology than referral cytology results without colposcopic guidance. More severe lesions were also detected more accurately.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Cervical cancer screening; Cervical intraepithelial neoplasia (CIN); Dysplasia; High-grade squamous intraepithelial lesion (HSIL); Low-grade squamous intraepithelial lesion (LSIL); Pap smear; Precancerous lesions of the cervix